Assessment of Effective Renal Plasma Flow, Enzymuria, and Cytokine Release in Healthy Volunteers Receiving a Single Dose of Amphotericin B Desoxycholate - Pai, Manjunath P.; Norenberg, Jeffrey P.; Telepak, Robert A.; Sidney, David S.; Yang, Shu (Antimicrobial Agents and Chemotherapy, 2005)
A correction has been published Classifications Services AAC Citing Articles Google Scholar PubMed Related Content Social Bookmarking CiteULike Delicious Digg Facebook Google+ Mendeley Reddit StumbleUpon Twitter current issue AAC About AAC Subscribers Authors Reviewers Advertisers Inquiries from the Press Permissions & Commercial Reprints ASM Journals Public Access Policy AAC RSS Feeds 1752 N Street N.W. • Washington DC 20036 202.737.3600 • 202.942.9355 fax • journals@asmusa.org Print ISSN: 0066-4804 Online ISSN: 1098-6596 Copyright © 2014 by the American Society for Microbiology. For an alternate route to AAC .asm.org, visit: AAC